Ethics, Evolution and Biblical Criticism in the Thought of Benjamin Jowett and John William Colenso - Hinchliff, Peter (The journal of ecclesiastical history, 1986)
With one minor exception, it was not much more than a series of coincidences which linked Jowett and Colenso. The one exception was when Colenso was in England after being excommunicated by Robert Gray, bishop of Capetown, as metropolitan. Samuel Wilberforce refused to allow Colenso to function in the diocese of Oxford but Jowett invited him to preach in Balliol chapel, which was not under the bishop's jurisdiction. Apart from this there seems to be no evidence of direct personal contact between the two men.